Trend of Poverty among Elderly: Evidence from Household Income Surveys - Mohd, Saidatulakmal; Senadjki, Abdelhak; Mansor, Norma (Taylor & Francis, 2018)
Elderly poverty is a major concern because of the changing in demographic pattern and the fact that elderly people have limited capacity and capability to prolonged employment. This article investigates poverty incidence among people who are elderly and nonelderly in Malaysia and analyzes the factors influencing elderly poverty. This article uses household income surveys of 2009 and 2012. Data indicates that poverty incidence among elderly heads of households is relatively low. Elderly poverty is high among elderly’s female head of household, other marital status, rural area, no or informal education, live alone, not working and in states whose main economic activity is agriculture.